If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+4(x+1)-2(x-3)=1
We simplify the equation to the form, which is simple to understand
x+4(x+1)-2(x-3)=1
Reorder the terms in parentheses
x+(+4x+4)-2*(x-3)=1
Remove unnecessary parentheses
+x+4x+4-2+*(+x-3+)=+1
Reorder the terms in parentheses
x+4x+4+(-2x+6)=1
Remove unnecessary parentheses
+x+4x+4-2x+6=+1
We move all terms containing x to the left and all other terms to the right.
+1x+4x-2x=+1-4-6
We simplify left and right side of the equation.
+3x=-9
We divide both sides of the equation by 3 to get x.
x=-3
| 6(3-t)=-27 | | -7a+9=49 | | -5=x-17 | | -185.00+35.00x=070.00-50.00x | | 5*2=9 | | 8r+7-6r-5= | | 4x+3(x-4)-(x+2)=6 | | 5p-25=2 | | F(4)=18x+14 | | 9s+4=148 | | 6-Y=11 | | -7x^2+3x=0 | | 6x-38=52+11x | | -2(3x-7)=6x+14 | | 3m^2+14m+58=0 | | -17r=102 | | -5-3(-6+x)-7x=-7 | | 2-4x=10x-28 | | 5x(x-6)=-50 | | 3(5x-1)-2(2x-18)=10x+6 | | 4x+-y=2 | | abs(2x-3+y)+abs(x-2y+3)=0 | | (12+a)+14=a | | 3-8(8+x)+9x=-60 | | 4b+b-8=4 | | (1.5*8.40)*7=x | | 2x(1+y^2)dxy(1+2x^2)dy=0 | | 4a^2-3a^2=400 | | (13*X)+(87*Y)=185 | | 3x+15=4-2x | | 3*X^2-5*X=Y^2-3*Y | | 0.3x-1.5=4.5x+2.9 |